A novel hybrid-energy heat pump with refrigerant injection: Performance characterization and injection optimization. (15th March 2020) - Wu, Wei; Leung, Michael
Highlights: A novel hybrid-energy heat pump (HEHP) with refrigerant injection is proposed. The flexible HEHP can gradually transform from absorption cycle to compression cycle. Refrigerant injection can reduce the driving temperatures by a simple configuration. COP increases with refrigerant injection ratio, reaching 17.19 42.34 with an injection ratio of 0.8 for the two HEHPs. Primary energy efficiency is up to 1.62 with optimal compression ratios of 1.4 2.5. Abstract: Heat pumps have been widely used for space heating towards sustainable buildings. Thermally-driven absorption heat pumps can greatly reduce electricity consumption but suffer from low reliability, low applicability or low efficiency under some circumstances. To address these problems, this study proposes a novel hybrid-energy heat pump (HEHP) with refrigerant injection, offering a high flexibility to gradually transform from an absorption cycle to a compression cycle. The refrigerant injection can reduce the required driving temperatures of the absorption sub-cycle, aiming to utilize energy with lower temperatures. Thermodynamic models have been established with verified accuracy to characterize the heating capacity, COP (coefficient of performance) and PEE (primary energy efficiency) under various refrigerant injection ratios ( RAHP ) and injection pressure ratios ( CR ). Results show that the constant-frequency HEHP yields more stable heating capacities while the variable-frequency HEHP yields more stable COPs. The COP increases significantly with RAHP, reaching 17.19 42.34 with a RAHP of 0.8 for the two HEHPs. As the CR increases, the heating capacity increases and the COP decreases, while the PEE decreases under better conditions (high Tgin and Tein ). After injection optimization, the optimal CR is found to increase significantly as Tgin or Tein decreases, with maximum CR of 1.4 2.5. The maximum PEEs are 0.99 1.62, 1.02 1.52, 1.04 1.48, and 1.045 1.46 for RAHP of 0.2, 0.4, 0.6, and 0.8, respectively. The turning Tein from which a higher RAHP yields higher maximum PEEs rises from −10 °C to 8 °C as Tgin increases from 100 °C to 130 °C.